Photovoltaic power prediction based on sliced bidirectional long short term memory and attention mechanism - Chen, Wengang; He, Hongying; Liu, Jianguo; Yang, Jinbiao; Zhang, Ke; Luo, Diansheng (Frontiers in Energy Research, 2023)
Solar photovoltaic power generation has the characteristics of intermittence and randomness, which makes it a challenge to accurately predict solar power generation power, and it is difficult to achieve the desired effect. Therefore, by fully considering the relationship between power generation data and climate factors, a new prediction method is proposed based on sliced bidirectional long short term memory and the attention mechanism. The prediction results show that the presented model has higher accuracy than the common prediction models multi-layer perceptron, convolution neural network, long short term memory and bidirectional long short term memory. The presented sliced bidirectional cyclic network has high prediction accuracy by low RMSE and MAE of 1.999 and 1.159 respectively. The time cost is only 24.32% of that of long short term memory network and 13.76% of that of bidirectional long short term memory network.